The Implementation of The Flipped Classroom for Early Grade Students in Elementary School - Hidayah, Lejar Retno; Mustadi, Ali (International Journal of Elementary Education, 2021)
The educational paradigm in the 21st-century coronavirus pandemic requires a deeper research study. This study aims to improve the mathematics learning outcomes of grade 1 students using the flipped classroom model and to find out their responses to the use of this model. The subjects of this study were 7 students who were grade 1 student. The research design used classroom action research consisting of planning, implementing, observing, and reflecting. Data were analyzed descriptively with qualitative and quantitative approaches. The results showed that the pre-cycle average value was 59, and an increase in cycle I became 77 and then 90 in cycle II. The minimum criteria are > 70 so that the cycle is stopped in the second cycle. Student responses in using this model, in general, can be said to be positive. Where most stated that the application of this model made it easier to learn mathematical material, increased self-confidence, learning flexibility, responsibility, active and free to choose learning styles. Although this model was not found to increase learning independence optimally, it can still be used to accommodate independent learning activities at home and train the learning independence of low-grade student.